2015 21st International Conference on Automation and Computing (ICAC) 2015
DOI: 10.1109/iconac.2015.7313992
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of experimental observation date for the development of mechanisms based creep damage constitutive equations for high chromium steel

Abstract: It is very important to design a safe factor or estimating the remain lifetime for electric power plant components of steam pipes which mostly manufacture by high chromium steels and work at high temperature and low stress level. The author will develop the mechanisms based on creep damage constitutive equations for high chromium steel under lows stress in initial stage: (1) Creep cavities mostly formed attaching with the precipitation of Laves phase or on grain boundary for high chromium steel under low stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…The development of a set of creep damage constitutive equations suitable for long term service is one of the key research activities and it has been very active, for example [5][6]. Within this context, the authors initiated and carried out research work on the development of a set of creep damage constitutive equations for high Cr creep resistant steel suitable for long-term service [7][8]. Here, the long-term service in time and lower stress in load is interchangeable.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The development of a set of creep damage constitutive equations suitable for long term service is one of the key research activities and it has been very active, for example [5][6]. Within this context, the authors initiated and carried out research work on the development of a set of creep damage constitutive equations for high Cr creep resistant steel suitable for long-term service [7][8]. Here, the long-term service in time and lower stress in load is interchangeable.…”
Section: Introductionmentioning
confidence: 99%
“…During research [8], three major sub-tasks were identified as: 1. The relationship of the minimum creep strain rate and a wider stress level; 2.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations